When i'm dead eaudiobook A black harbor novel. - Morrissey, Hannah (Black Harbor Novels, 2023)
This program features multicast narration. One girl murdered...another one missing...and a medical examiner desperate to uncover the truth in When I'm Dead , the latest Black Harbor mystery by acclaimed author Hannah Morrissey. On a bone-chilling October night, Medical Examiner Rowan Winthorp investigates the death of her daughter's best friend. Hours later, the tragedy hits even closer to home when she makes a devastating discovery—her daughter, Chloe, is gone. But, not without a trace. A morbid mosaic of clues forces Rowan and her husband to question how deeply they really knew their daughter. As they work closely to peel back the layers of this case, they begin to unearth disturbing details about Chloe and her secret transgressions...details that threaten to tear them apart. Amidst the noise of navigating her newfound grief and reconciling the sins of her past, an undeniable fact rings true for Rowan: karma has finally come to collect. A Macmillan Audio production from Minotaur Books.